Desarrollo de una tienda virtual usando CMS open source para la empresa DataMarket de la ciudad de Machala, provincia de El Oro - Martínez Añazco, Gabriela Noemí (2010)
This thesis has the general objective to develop a virtual store for DataMarket company of the city of Machala, province of El Oro, using Open Source CMS to offer products, improve sales and enhance the customer.